Magic as a Form of Oppression Towards Women: Gender Ideology in Maleficent (2014) - Wendranirsa, Thalia Shelyndra (UI Scholars Hub, 2014)
Previous studies propose that female protagonists in Disney movies are represented based on gender construction that causes oppression towards women, but in 2014, Disney produces Maleficent which offers different characterization and theme opposing the aforementioned gender construction. By focusing on its different female main character and theme, this paper aims to see what kind of oppression occurs and how Disney presents their gender ideology in the movie. The findings reveal that even though Maleficent is portrayed as a powerful woman, she is also oppressed. Her magical power becomes a trigger of her oppression since men consider Maleficent’s power as a threat for their domination. This research gives an insight to see gender ideology in Disney movies which is still considered as an arguable issue among the society.